Relationship-based early intervention services for children with complex needs: lessons from New Zealand. Issue 4 (19th December 2016) - Blackburn, Carolyn
Abstract : Purpose: A case study is reported of a relationship-based early intervention (EI) service for children with complex needs in New Zealand. The purpose of this paper is to explore parent and professional views and perceptions about the key characteristics of a relationship-based EI service. Design/methodology/approach: This qualitative study involved interviews and observations with 39 participants (10 children, 11 parents and 18 professionals). Findings: Parents appreciated the knowledgeable, well-trained professionals who invested time in getting to know (and love) children and families and family practices, worked together in harmony and valued the contribution that parents made to their child's progress and achievement. Professionals described the key characteristics of the service in terms of the range of therapies offered by the service, the focus on a strengths-based and family-focussed approach, play-based assessments, acceptance and value of family practices (including responsiveness to Maori and bi-culturalism), appropriate and respectful places to meet and greet families and work with children, and recruitment and retention of humble professionals who identified with the ethos of the model. Observable social processes and structures within the delivery of the model include respectful professional interactions and relationships with children and families, integrated professional working, effective and timely communication between professionals and families, pedagogy of listening, waiting and personalisation, engaged families and actively participating children. Originality/value: This case study emphasises the significance of professional love and relational pedagogy to EI services and the value of this to improving parent-child relationships and children's long-term outcomes.